Multimorbidity patterns and their associated factors among patients with type 2 diabetes in China: A hospital-based observational study - Jin Li; Hou Hou; Yong Zhang; Jing Li (Heliyon)
Introduction: Most patients with type 2 diabetes mellitus (T2DM) suffer from multimorbidity, but the multimorbidity patterns were not well understood. We aimed to ascertain the different multimorbidity patterns among T2DM patients and to explore the corresponding associated factors. Method: The study included 3403 T2DM patients from Tianjin, China. Multimorbidity (including dyslipidemia, hypertension, hyperuricemia, cardiovascular diseases, chronic kidney disease, and chronic liver disease) was ascertained through medical records. Data were analyzed using latent class analysis and multi-nominal logistic regression. Results: The leading 3 morbidity were dyslipidemia, cardiovascular diseases, and hypertension; and 16.9 % had multimorbidity. Four unique patterns were ascertained: multimorbidity-free, T2DM with cardiovascular diseases mainly, T2DM with dyslipidemia mainly, and T2DM with hypertension mainly. In the subsample of 1779 patients, greater BMI and LDL, and non-use of insulin were associated factors for cardiovascular disease patterns; older age, higher HDL, lower LDL, and insulin use for dyslipidemia patterns; male sex, higher TG and LDL, and non-use of insulin for hypertension patterns. Conclusions: Dyslipidemia, cardiovascular diseases, and hypertension were the most common chronic conditions among T2DM patients. Four groups of T2DM-associated multimorbidity patterns were identified, and different patterns had varying associated factors. Our research findings highlight the significance of formulating personalized nursing measures for patients with different T2DM multimorbidity patterns.